Late Triassic–early Jurassic continental extension in southwestern Gondwana: tectonic segmentation and pre-break-up rifting - Franzese, Juan R.; Spalletti, Luis A. (Journal of South American earth sciences, 2001)
From the earliest Jurassic to the Cenozoic, the Neuquén Basin (central Argentina and Chile) evolved as an intra-arc and transarc–retroarc depression through the gradual development of the Andean magmatic arc. However, the region adjacent to the proto-Pacific margin of Gondwana between 30 and 40°S was subject to pre-Andean continental extension that began in the Late Triassic and lasted about 30 million years until the Early Jurassic. This extension resulted in the generation of a series of rifts oriented parallel to the margins of the extended area and characterized by continental volcaniclastic and pyroclastic deposits associated with lava flows and bimodal plutonic intrusions. The inception of the Neuquén Basin as a single depocenter occurred in the Early Pliensbachian, when post-rift thermal subsidence led to a general marine transgression. The T–J extension is closely linked to structures created by previous tectonothermal episodes such as the development of a Carboniferous–Permian orogenic belt (330–280 Ma), and to events along the proto-Pacific margin of Gondwana. Lithospheric thickening related to Late Paleozoic convergence caused strong gravitational instability in the orogenic belt between 30 and 40°S. Subsequent cessation of subduction, coeval with establishment of dextral strike-slip tectonics parallel to the continental margin, caused detachment of the subducting slab and generation of an asthenospheric window. Anomalous heating of the upper mantle resulted in bimodal magmatism, uplift, thermal weakening, and gravitational collapse of the upper crust. South of this extended area, proto-Pacific subduction was active during the same Late Triassic–Early Jurassic interval. Thus, the contrasting tectonic behaviour of the Gondwana margin north and south of 40°S suggests significant pre-Andean tectonic segmentation that coincides with the southern boundary of the area extended in the Late Triassic–Early Jurassic. Previous intepretations assumed a common massive extension in the Andean and Patagonian regions of southern South America. Our results demonstrate that T–J extensional rifting and magmatism between 30 and 40°S were the result of mechanical interaction between different lithospheric plates at the pre-Andean (proto-Pacific) continental margin. On the other hand, the mechanical and thermal processes that affected much of Patagonia during the Middle and Late Jurassic were a response to the tectonic and magmatic processes that caused the initial break-up of Gondwana with the opening of the Weddell Sea after 180 Ma.